Modelling the effects of intervention measures in reducing the risk of norovirus transmission in preschool settings. - Edward Lee; Benjamin Er; Joanna Khoo; Sheot Harn Chan; Kyaw Thu Aung (PLoS ONE)
Singapore has seen an increase in norovirus outbreaks in preschools from 2019 to 2022 primarily due to person-to-person transmission. This study describes the use of compartmental susceptible-exposed-infectious-recovered (SEIR) modelling to simulate the spread of norovirus among preschool children in a classroom setting. Different intervention measures, such as isolation of infected preschoolers, handwashing and surface decontamination were modelled to quantify their effectiveness at reducing the number of children infected. We found that isolation of the sick child was the most effective single intervention to reduce transmission risk, which was 5 times more effective than handwashing. Coupled with handwashing and surface decontamination, transmission risk could be further reduced, close to zero. Findings from our study can be used to reiterate to parents and teachers on the importance of recognizing the symptoms exhibited by their unwell children and refraining from sending them to school, as this action poses a risk of transmitting norovirus to other children. In addition, our findings can be used to educate children and staff in preschools on the importance of practising good personal hygiene and regular environmental cleaning. Through this study, decision makers would be better informed on the effectivness of various risk mitigation measures at reduce the risk of norovirus transmission in preschool settings.